Oscillation detection in process industries – Part II: Industrial application. (June 2019) - Dambros, Jônathan W.V.; Trierweiler, Jorge O.; Farenzena, Marcelo; Kempf, Ariel; Longhi, Luís G.S.; Teixeira, Herbert C.G.
Abstract: This work is the second of a two-part study on oscillation detection in process industries. The first part, in short, extensively reviews and classifies the detection techniques. In this part, techniques are selected and evaluated on two industrial data sets, the first extracted from the literature and the second from a refinery. Common detection problems are pointed out aiming to drive future better-grounded researches on the topic. Based on the evaluation, features of interest of the detection methods, recommended test for new methods, and a new approach based on the verdict of multiple techniques are proposed. The work finalizes by pointing out research opportunities.